The SME Condition During Covid 19 Pandemic: Financial And Business Overview - Rahmina Suryani, Khalisa; Rizka Zulfikar; Aida Vitria (Publisher Cv. Inara, 2021)
The Covid-19 outbreak has become a global problem and has caused economicproblems in various sectors including the SME sector. This research was conductedto examine the impact of the Covid-19 pandemic on the business conditions of SMEswhich later can be used by policy makers in determining the right actions toovercome financial problems in the SME sector.This research was conducted in the province of South Kalimantan using primarydata. Sampling was done by purposive sampling with an instrument in the form of aquestionnaire. This study used a sample of 233 respondents. The data analysistechnique was performed using the analysis of the validity and reliability of theinstrument and quantitative descriptive analysis to describe the financial conditionsof SMEs and the affected business / corporate sectors. The results of this study foundthat (1) There was a significant difference to the financial condition of SMEs beforeand after the pandemic, where there was a decrease in gross income (-41.6%) andthe level of profit in the SME sector (-62.8%) in general (2) Some of the impacts ofthe Covid Pandemic -19 regarding the business conditions of SMEs, namely (a)there are still many SMEs that have not been able to sell online, (b) there has beenan increase in raw materials, (c) the majority of SMEs have difficulty obtaining rawmaterials, (d) there is a decrease in motivation and work productivity which issignificant, (e) there are still many SMEs that experience a shortage of cash andmany SMEs are in arrears of liabilities, (f) but the majority of SMEs still believethey will survive and pass the pandemic.